A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
Given that f(x) = 5x – 10 and g(x) = x + 3, solve for f(g(x)) when x = –1.
–30
0
10
12
anonymous
 one year ago
Given that f(x) = 5x – 10 and g(x) = x + 3, solve for f(g(x)) when x = –1. –30 0 10 12

This Question is Closed

freckles
 one year ago
Best ResponseYou've already chosen the best response.0notice g(x)=x+3 enter in 1 for x

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0actaully is hmm 1 well

freckles
 one year ago
Best ResponseYou've already chosen the best response.0your work isn't meaningless though it is good example

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0\(\bf f(x)=5x10\qquad g(x)=x+3 \\ \quad \\ f(\quad {\color{brown}{ g(x)}} \quad )=5{\color{brown}{ g(x)}}10\implies f(\quad {\color{brown}{ g(x)}} \quad )=5{\color{brown}{ (x+3)}}10 \\ \quad \\ f(\quad {\color{brown}{ g({\color{blue}{ 1}})}} \quad )=5{\color{brown}{ g({\color{blue}{ 1}})}}10\implies f(\quad {\color{brown}{ g({\color{blue}{ 1}})}} \quad )=5{\color{brown}{ ({\color{blue}{ 1}}+3)}}10\)
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.